A categorization of the consequences of entrepreneurial failure - Validated in Hungary [Vállalkozói kudarc következményeinek rendszerezése – Magyarországon validálva] - Repisky Máté (VEZETÉSTUDOMÁNY, 2023)
Uncertainty and risk are basic elements of entrepreneurial life, and consequently, most entrepreneurs will experience failure, which can impact their lives in various ways. Although several previous studies have tried to categorize the consequences of failure, none could cover their full range. Therefore, the main objective of this qualitative, narrative research was to build a useable categorization system for the consequences of entrepreneurial failure. As a result of this theoretical- and sixteen-interview-based research, the consequences of entrepreneurial failure can be categorized into six groups (and twenty-four sub-groups): financial, psychological, social, professional, legal and physiological consequences. Based on the results, failure is not a negative experience for all entrepreneurs; in fact, for many, negative and positive consequences balanced each other out, or they were not impacted by the failure. During the analysis, potential connections between categories of consequences and the identification of root consequences are also presented.